Water Exchange Between the Gulf of Ob and the Kara Sea During Ice-Free Seasons: The Roles of River Discharge and Wind Forcing - Osadchiev, Alexander; Konovalova, Olga; Gordey, Alexandra (Frontiers in Marine Science, 2021)
The Gulf of Ob is among the largest estuaries in the World Ocean in terms of area, watershed basin, and freshwater discharge. In this work, we describe the roles of river discharge and wind forcing on the water exchange between the Gulf of Ob and the Kara Sea during ice-free seasons. This work is based on the extensive in situ measurements performed during 10 oceanographic surveys in 2007–2019. Due to large river runoff (∼530 km3 annually) and low tidal forcing (<0.5 m/s), the estuarine processes in the Gulf of Ob during the ice-free season are generally governed by gravitational circulation. Local wind forcing significantly affects general estuarine circulation and mixing only in rare cases of strong winds (∼10 m/s). On the other hand, remote wind forcing over the central part of the Kara Sea regularly intensifies estuarine—sea water exchange. Eastern winds in the central part of the Kara Sea induce upwelling in the area adjacent to the Gulf of Ob, which increases the barotropic pressure gradient between the gulf and the open sea. As a result, intense and distant (120–170 km) inflows of saline water to the gulf occur as compared to the average conditions (50–70 km). Remote wind forcing has a far stronger impact on saltwater intrusion into the Gulf of Ob than the highly variable river discharge rate. In particular, saltwater reaches the shallow central part of the gulf only during upwelling-induced intense inflows. In the other periods (even under low discharge conditions), fresh river water occupies this area from surface to bottom. The upwelling-induced intense inflows occur on average during a quarter of days (July to October) when the gulf is free of ice. They substantially increase the productivity of phytoplankton communities in the gulf and modify the taxa ratio toward the increase of brackish water species and the decrease of freshwater species.